THE EFFECT OF THE ADDITION OF 2-MERCAPTOBENZOTHIAZOLE TOWARDS THE EFFECTIVITY OF SODIUM MOLYBDATE AS CORROSION INHIBITOR FOR CARBON STEEL IN 1% NACL SOLUTION - DWI BONITA PASARIBU ( NIM : 10508103); Pembimbing : Dr. Bunbun Bundjali, APRINI
Carbon steel is widely used in oil and gas industry as material for pipeline used to divert crude oil and natural wet gas. In this fluid environment, the inner part of pipeline may be corroded. To inhibit the corrosion rate, corrosion inhibitor is injected periodically into the fluids. In this study, sodium molybdate and 2-mercaptobenzothiazole (MBT) were used as corrosion inhibitor. Compared to chromate, sodium molybdate inhibitor is less toxic and more eco-friendly. Investigation of the effectivity of these inhibitors in 1% NaCl solution was tested at 30, 45, and 60oC with the variation of concentration of sodium molybdate was 5, 10, 15, 20, and 25 ppm, and 2-mercaptobenzothiazole with the variation of concentration of 2, 4, 6, 8, and 10 ppm. Weight loss method, Electrochemical Impedance Spectroscopy, and extrapolation Tafel method were used to measure the corrosion rate. At 60oC, the inhibition efficiency of 25 ppm sodium molybdate is 35.7%. The addition of 10 ppm MBT increased the inhibition efficiency to 79.4%. Sodium molybdate has low inhibition efficiency for carbon steel in acid media and the addition of MBT can increase the effectiveness of sodium molybdate in inhibiting corrosion rate of carbon steel not only at low temperature, but also at high temperature.